Acetic Acid Content in Salak Sidempuan Vinegar - Dilla Wirmaningsih; Yusni Atifah; Helendra (Jurnal Serambi Biologi, 2023)
Acetic acid is the result of natural fermentation derived from processed fruits and vegetables. Sidempuan salak fruit (Salacca sumatrana) is a salak that has a very large water content and can be processed into processed vinegar, one of which is Sidempuan salak vinegar. This study was conducted through anaerobic fermentation using Saccharomhyces cerevisiae for seven days, then re-fermented aerobically using Acetobacter xylinum for nine days aimed at converting alcohol and producing acetic acid. To determine the level of acetic acid, it uses a quantitative test with an alkalimetric titration method using a 0.1 N NaOH solution and a 1% phenolphthalein indicator of three drops, then replicating three times to cause a pink color. Thus, the results were obtained from measuring acetic acid levels produced from the fermentation of Sidempuan salak vinegar of 4.8% and having a pH of 4. This result proves that acetic acid produced from the fermentation of Sidempuan salak vinegar has met the criteria for vinegar content that can be marketed and is suitable for public consumption.